ANALYSIS OF THE ECONOMIC SIGNIFICANCE OF AGRICULTURE IN THE REPUBLIC OF SERBIA AND THE REPUBLIC OF CROATIA - Gordana Radović; Vesna Gantner; Jonel Subić (Ekonomika Poljoprivrede (1979))
The aim of the paper is to analyze the economic significance of agriculture in Serbia and Croatia. Bearing in mind the similarities in the characteristics of agricultural production, as well as the economic characteristics of agricultural entities, the authors of the research start from the hypothesis that agriculture has approximately the same economic significance in the current period in both countries. In order to verify the hypothesis, the paper analyzes the relevant macro-economic indicators. For this purpose, the following methods are used: desk research, descriptive statistics, analysis and synthesis, as well as the comparative method. The authors conclude that in recent years the participation of agriculture in the gross domestic product has recorded a downward trend in both countries, as well as the participation of the number of employees in agriculture in the total number of employees. Based on the conducted research, the authors conclude that agriculture has a decreasing economic significance and in Serbia and in Croatia.